A Deleuzian Reading on Hart’s Internal Point of View - Harison Citrawan (Faculty of Law, Universitas Padjadjaran, 2022)
Reading H.L.A Hart’s internal point of view or participant’s self-understanding through Deleuzian philosophy suggests an alternate way of grasping Hart’s refutation of John Austin’s command-based theory of law. The study claims two main arguments. First, a Deleuzian investigation of participants’ self-understanding asserts the way to understand not only what law is but also what is about law, or, to be precise, what law can actually do. Therefore, Hart’s participant’s self-understanding is not simply a property of law but instead, it is a concept that uncovers the capacity of Deleuzian ‘desiring-machines’ in law’s plane of immanence. Second, by putting Hart’s concept to the initial proposition of refutation of Austinian mere habit of obedience, we can situate the participants as desiring-machine whose acceptance to rule is essentially a form of communications. That is, like a rhizome, it has no definite root/source. Self-understanding or acceptance does not stem from a particular sovereign power—it somehow reflects Deleuze’s transcendental empiricism.DOI: https://doi.org/10.22304/pjih.v9n1.a7